Recognition, Rights and Redistribution: Introduction to the Honorary Issue of Intersections. EEJSP to Celebrate Júlia Szalai - Neményi, Mária; Messing, Vera; Szikra, Dorottya (Intersections. East European Journal of Society and Politics, 2018)
This special issue of Intersections. EEJSP is dedicated to some of the central concerns of contemporary sociology: recognition, rights, and redistribution. These are three interrelated and often contrasted subjects that have occupied a special place in the works of Júlia Szalai, one of Hungary’s leading sociologists. Szalai, besides being an early pioneer of sociological research in her own country, is also well known outside Hungary for her international and comparative investigations of inequality and poverty, her research on ethnic minorities, and especially the Roma, as well as her work on the welfare state. Her research has involved close co-operation with colleagues from all over Europe from Scotland to Sweden, from Slovakia to Romania and Serbia. This is why, besides a special issue being dedicated to her in Socio.hu: Social Science Review in Hungarian, a ‘twin-issue’ of Intersections. EEJSP is also being published to allow her friends and colleagues from around Europe to celebrate Júlia Szalai on her birthday. Intersections. EEJSP and Socio.hu are both on-line social science journals based within the Hungarian Academy of Sciences where Szalai started her research career in the 1970s, and where she has served as Professor Emerita in recent years while also teaching and undertaking research at the Central European University. These two journal special issues thus also symbolize the gratitude of the Center for Social Sciences, and within this, the Institute for Sociology, to Szalai for the teaching and inspiration her colleagues and friends have received from her for nearly half a century.